The upcycled self : a memoir on the art of becoming who we are - Black Thought, 1973-; Martin, Jasmine (One World, 2023)
Through vivid vignettes, the platinum-selling, Grammy-winning co-founder of The Roots tells dramatic stories of the four powerful relationships that shaped him, each a complex weave of love, discovery, trauma and loss, illuminating the redemptive power of the upcycle.